Pengaruh Media Pembelajaran Video Animasi Materi Bahaya Merokok Terhadap Hasil Belajar Siswa Kelas 5 SD - Nila Latifaturrohmah; Dya Ayu Agustina Putri; Leny Suryaning Astutik (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2025)
The purpose of this study is to ascertain how employing animated video content affects fifth-grade students' learning outcomes on the risks of smoking at SDN 3 Mojosari. The research findings indicate that the pre-test p-value was 0.384, suggesting no significant influence of animated video media on students' learning outcomes before the intervention. However, the post-test results revealed a p-value of <0.001, indicating a strong and positive effect of animated video media on students' learning outcomes. The use of appropriate learning media enhances students' understanding and improves their learning results. Animated videos captivate students' interest by integrating visual and auditory elements, thereby enriching the learning experience and enhancing student involvement in understanding the dangers of smoking. The findings demonstrate that animated video content significantly improves the learning results of fifth-grade students at SDN 3 Mojosari.